Rapid patterning of single-wall carbon nanotubes by interlayer lithography. - Leem, D; Kim, S; Kim, J; Sohn, J; Edwards, A; Huang, J; Wang, X; Kim, J; Bradley, D; Demello, J (2010)
High resolution patterning of single-wall carbon nanotubes is achieved using interlayer lithography. Minimum feature sizes of 6 and 0.7 μm are demonstrated on glass and silicon, using the negative photoresist SU-8 and the positive photoresist AZ7220, respectively. Films patterned using SU-8 have a good balance of transparency and sheet-resistance, and are shown to be effective electrodes for organic solar cells. Copyright © 2010 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.